The challenge of communicating corporate sustainability on website: the role of dialogic potential - Herrada-Lores, Sara; Estrella-Ramón, Antonia; Iniesta-Bonillo, M. Ángeles (Journal of Business Economics and Management, 2025)
With the growing social concern for corporate sustainability, organizations are under increasing pressure to communicate their sustainability efforts transparently and effectively. Websites, driven by their participatory nature, have emerged as pivotal platforms for such communication and a key relational tool. This study explores the role of website communication in fostering dialogic potential to facilitate two-way communication on sustainability issues. This research delves into the level of two-way communication of websites, which is determined by a suitable management of sustainability content and the presence of interactive features. Specifically, this study aims to identify boundaries in website design features that influence the effectiveness of sustainability communication. To this end, a novel measurement instrument, the Two-Step Index, has been designed to provide a comprehensive and in-depth assessment of the dialogic potential of websites. Few studies have explored the dialogic potential of websites for sustainability communication highlighting the need to uncover limitations and gaps in current practices. The findings reveal a low level of dialogic potential in corporate sustainability communication on the sampled websites, with a stronger emphasis on content management than on interactivity. Based on these results, practical insights are provided, along with specific actions to facilitate the implementation of dialogic strategies on websites.